2009
DOI: 10.1194/jlr.p900001-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase IA polymorphism P479L is common in Greenland Inuit and is associated with elevated plasma apolipoprotein A-I

Abstract: Carnitine palmitoyltransferase IA, encoded by CPT1A, is a key regulator of fatty acid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 33 publications
(41 reference statements)
2
50
1
5
Order By: Relevance
“…We chose to relax our MAF criteria to include SNPs with MAF > 0.01 to genotype tagging SNPs in the CPT1A gene that may be common (MAF у 0.05) in Yup'ik Eskimos despite being rare (MAF < 0.05) in CEU and CHB populations. We also included the nonsynonymous P479L (rs80356779) CPT1A SNP for genotyping based on previous associations with elevated plasma HDL-cholesterol and apolipoprotein A-I levels in the Greenland Inuit ( 35 ). Genotyping of the 28 SNPs, including P479L, was carried out by allele-specifi c primer extension of multiplex amplifi ed products and detection using matrix-assisted laser desorption ionization time-of-fl ight spectrometry on a Sequenom iPLEX platform at the Broad Institute ( 41 ).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
See 3 more Smart Citations
“…We chose to relax our MAF criteria to include SNPs with MAF > 0.01 to genotype tagging SNPs in the CPT1A gene that may be common (MAF у 0.05) in Yup'ik Eskimos despite being rare (MAF < 0.05) in CEU and CHB populations. We also included the nonsynonymous P479L (rs80356779) CPT1A SNP for genotyping based on previous associations with elevated plasma HDL-cholesterol and apolipoprotein A-I levels in the Greenland Inuit ( 35 ). Genotyping of the 28 SNPs, including P479L, was carried out by allele-specifi c primer extension of multiplex amplifi ed products and detection using matrix-assisted laser desorption ionization time-of-fl ight spectrometry on a Sequenom iPLEX platform at the Broad Institute ( 41 ).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…In a cross-sectional cohort of French-Canadians, Robitaille et al reported an association between the nonsynonymous A275T (rs17610395) SNP with BMI ( P = 0.05) and waist circumference ( P = 0.008) only after accounting for dietary fat intake ( 53 ). Finally, in Greenland Inuit, Rajakumar et al showed the L479 allele in the nonsynonymous P479L variant was associated with elevated fasting HDL-cholesterol and ApoA1 levels ( 35 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Как известно, главны-ми продуктами питания эскимосов, а также береговых чукчей и коряков издревле были мясо и жир ластоногих и китов. Несмотря на жирную пищу, в сыворотке крови представителей этих народов наблюдаются довольно низкие уровни холестерина и липидов, что, по-видимому, свидетельствует о том, что в эволюции коренных наро-дов Крайнего Севера важную роль играли сопряженные процессы адаптации к диете и экстремальным факторам среды (Rajakumar et al, 2009;Lemas et al, 2012).…”
unclassified